Utilization of Capital Budgeting Techniques and Their Impact on the Financial Stability of Manufacturing Firms in Bulan, Sorsogon - Bongalonta, Michael B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examines the utilization of capital budgeting techniques and their impact on the financial stability of manufacturing firms in Bulan, Sorsogon. It focuses on how decision-making tools such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP) shape financial outcomes in terms of liquidity, solvency, and equity strength. Findings show that manufacturing firms rely heavily on the Payback Period, while the application of more advanced methods like NPV and IRR remains limited. Although businesses demonstrate fair liquidity and solvency, their financial structures are highly debt-dependent, exposing them to long-term risks. Regression analysis confirmed that firms using advanced techniques achieve stronger financial stability, while those dependent on simple payback evaluations are more vulnerable to short-term pressures and weaker growth prospects. The study highlights the need for strengthening equity financing, enhancing financial literacy, and adopting sophisticated capital budgeting methods to improve long-term stability. By providing empirical evidence from a local manufacturing context, this research contributes to both practice and scholarship, underscoring that advanced capital budgeting tools not only optimize investment decisions but also safeguard firms against financial vulnerability.